Closed Reduction Conversion of a Dual Mobility Dislocation to an Intraprosthetic Dislocation - Mesko, Daniel; Higuera, Carlos; Bloomfield, Michael (The Journal of Hip Surgery, 2017)
Building on a paucity of prior reported cases, we report on a patient with an off-label dual mobility liner, who sustained a dislocation. Following closed reduction in the emergency room, catching/grinding was felt, and imaging confirmed an intraprosthetic dislocation (IPD). This required revision hip arthroplasty. Dual mobility dislocations have the unique risk of conversion to IPDs during closed reduction attempts. There should be a low threshold to perform closed reductions in the operating room (OR) setting by an orthopaedic surgeon under full relaxation/sedation to optimize success and reduce the risk of creating an IPD.
Keywords: intraprosthetic dislocation; dual mobility; closed reduction